Morphological and Biochemical Characteristics of a Novel Albino Tea Cultivar (Camellia sinensis ‘Geumda’) - Yun-Suk Kwon; Su Jin Kim; Ha Rim Hong; Byung-Hyuk Kim; Eun Young Song; Chun Hwan Kim; Liang Chen; Doo-Gyung Moon (Horticulturae)
Tea plant [Camellia sinensis (L.) O. Kuntze] is an economically important evergreen crop cultivated worldwide. While most tea plants have green leaves, albino cultivars with yellow or white young leaves have attracted growing interest due to their elevated levels of L-theanine, a key compound that enhances the umami flavor and overall quality of green tea. In this study, we characterized the morphological and biochemical traits of a novel albino tea cultivar, ‘Geumda’, developed in Korea. ‘Geumda’ exhibited yellow young shoots during the first flush and smaller leaves compared to the green-leaf standard cultivar, ‘Sangmok’. Although the catechin content of ‘Geumda’ was lower than that of ‘Sangmok’, it exhibited significantly higher levels of total amino acids, L-theanine, and arginine by 2.1-, 2.0-, and 9.8-fold, respectively. Transmission electron microscopy and gene expression analysis revealed that the elevated amino acid content in ‘Geumda’ was associated with impaired chloroplast development, leading to reduced chlorophyll content and diminished photosynthetic capacity. These findings suggest that ‘Geumda’, with its high concentrations of theanine and arginine and its impaired chloroplast development, represents a valuable genetic resource for the production of functional green teas enriched in umami flavor and beneficial health properties.